Direct action of intestinal microorganisms in colorectal cancer cell line - Bernacchia, Juliana Lourdes (2022)
Numerous evidences demonstrate the importance of the microbiome mainly due to its immunological action, in the development of multiple diseases, such as colorectal cancer (CRC). In agreement with previous works, bacteria such as Escherichia coli (E.coli) and Bacteroides fragilis, among others, have high prevalence in CRC patients compared to the normal population.In this work we investigate the possible pathways and signaling that may contribute to CRC development that could be affected by direct action of bacteria over colorectal cancer cells, in the absence of additional signals from the immune system. Therefore, we first determined the total amount of genes that were up or down regulated (log FC >1 or <-1), as determined by RNAseq, in experiments where the CRC cell line DLD-1 was infected with the bacteria E.coli for 2 h or Enterotoxigenic Bacteroides fragilis (ETBF) for 2 to 24 h at MOI: 500 (database GSE130152). Then, we performed an over-representation analysis using the ConsensusPathDB bioinformatic tool.We found that ETBF upregulates 525 genes involved in processes like cell migration, inflammatory response, and the FOXO-mediated transcription of cell cycle genes (at least p< 0.05). While E.coli upregulates 2249 genes, most of them involved in TNF, NF-kB, MAPK, and inflammatory signaling pathways (at least p< 0.05). Interestingly, 231 upregulated and 414 downregulated genes are shared with ETBF as determined by Venn diagrams. Then to confirm the previous suggested incidence of these bacteria in CRC, we analyzed the presence of both, using LDA score (linear discriminant analysis) in colorectal neoplasms from GMrepo database of human gut metagenomes and found that they have LDA>4, thus, strongly involved in CRC.We conclude, there are signals and pathways independent of the immune system that could be induced directly by bacteria in the epithelial colorectal cells, contributing to CRC.